Seeking Sepsis in the Emergency Department- Identifying Barriers to Delivery of the Sepsis 6. Issue 1 (5th May 2016) - Bentley, James; Henderson, Susan; Thakore, Shobhan; Donald, Michael; Wang, Weijie
Abstract : The Sepsis 6 is an internationally accepted management bundle that, when initiated within one hour of identifying sepsis, can reduce morbidity and mortality. This management bundle was advocated by the Scottish Patient Safety Programme as part of its Acute Adult campaign launched in 2008 and adopted by NHS Tayside in 2012. Despite this, the Emergency Department (ED) of Ninewells Hospital, a tertiary referral centre and major teaching hospital in Scotland, was displaying poor success in the Sepsis 6. We therefore set out to improve compliance by evaluating the application of all aspects of the NHS Tayside Sepsis 6 bundle within one hour of ED triage time, to identify what human factors may influence achieving the one hour The Sepsis 6 bundle. This allowed us to tailor a number of specific interventions including educational sessions, regular audit and personal feedback and check list Sepsis 6 sticker. These interventions promoted a steady increase in compliance from an initial rate of 51.0% to 74.3%. The project highlighted that undifferentiated patients create a challenge in initiating the Sepsis 6. Pyrexia is a key human factor-trigger for recognising sepsis with initial nursing assessment being vital in recognition and identifying the best area (resus) of the department to manage severely septic patients. EDs need to recognise these challenges and develop educational and feedback plans for staff and utilise available resources to maximise the Sepsis 6 compliance.